Comparative Metabolomic Analysis of the Nutrient Composition of Different Varieties of Sweet Potato - Xiaolin Wan; Xiuzhi Wang; Qiang Xiao (Molecules)
Sweet potatoes are rich in amino acids, organic acids, and lipids, offering exceptional nutritional value. To accurately select varieties with higher nutritional value, we employed liquid chromatography–tandem mass spectrometry (LC-MS/MS) to analyze the metabolic profiles of three types of sweet potatoes (white sweet potato flesh, BS; orange sweet potato flesh, CS; and purple sweet potato flesh, ZS). When comparing CS vs. BS, ZS vs. BS, and ZS vs. CS, we found differences in 527 types of amino acids and their derivatives, 556 kinds of organic acids, and 39 types of lipids. After excluding the derivatives, we found 6 amino acids essential for humans across the three sweet potatoes, with 1 amino acid, 11 organic acids, and 2 lipids being detected for the first time. CS had a higher content of essential amino acids, while ZS had a lower content. Succinic acid served as a characteristic metabolite for ZS, helping to distinguish it from the other two varieties. These findings provide a theoretical basis for assessing the nutritional value of sweet potatoes and setting breeding targets while facilitating the selection of optimal varieties for food processing, medicine, and plant breeding.